Perception of Response Efficacy and Residents’ Evacuation Response Intention among Flood-Prone River Niger Coastal Residents of Edo State - Igudia, Enoma Omorogieva; Hitlar, Denyinye Minna (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
The physical environment is increasingly becoming unsafe for human habitation as natural hazards especially weather-related ones increase in intensity and frequency, adversely impacting human lives and properties leading to what is generally termed as ‘natural disasters.’ Research on understanding human response behaviour to pre-warning cues especially to direct authorities’ directives is crucial effective conducting risk communication.  The purpose of this research work is to residents’ perception of response efficacy influences their evacuation intention. The descriptive survey design was employed. The study population covers all the households in the Four River Niger communities (Agenebode, Anebete, Udochi, Udaba-ekpere) all in Edo-North Senatorial District, Edo State who have been directed to evacuate to safer grounds. Two of them (Agenebode and Udaba-Ekpere) were randomly selected for the study. A sample size of 384 respondents was reached with the questionnaire instrument but only 358 of the retrieved items were fit enough to be used for the analysis representing about a 93% return rate. The questionnaire instrument is a researcher-structured questionnaire that was validated by three research experts and a Cronbach Alpha reliability of 0.872 was obtained after the validity and the removal of items that loaded poorly. Frequency counts and percentages were used to answer the raised research questions while Logistic Regression Statistics was used to test the formulated hypotheses at a 0.05 significant level. It was found that only 105 (29.30%) of the residents intended to evacuate to safer grounds which is about 30% while the rest about 253(70.70%) intend not to evacuate. Findings indicated that residents’ perception of response efficacy significantly influences their evacuation response intention (B = .257, p = .000), Consequently, the need to communicate and engage coastal residents based on consensus protection action among others were recommended. Keywords: Risk Communication, Climate Change, Protection Action, Response Efficacy, Evacuation Intentions.